Bris soil: natural vegetation and potential cultivated plants - Abu Bakar, Ainaa Eliah; Johari, Nursyafica Nadia; Mat Ali, Qurratu Aini; Othman, Rashidi (Nova Science Publishers, Inc., 2023)
In Peninsular Malaysia, sandy soils, sometimes called BRIS (Beach Ridges Interspersed with Swales) soils, are renowned for being located close to the coast. The monsoon season, which forms the sediment or sand carrying the coarse sand particles, is the source of BRIS soil. This soil strengthens the unique functions of the soil and can be used in the manufacturing of agricultural goods. Sand makes up >90% of the BRIS soil composition, which makes it suitable for agricultural usage. The number of cultivable plants in the chosen area can be used to identify the compatibility of the soil. However, it is important to study the fundamental requirements for improving the soil’s physical qualities to cultivate different crops. BRIS soil is classified as problematic soil since it needs to be handled traditionally, as it has a low ability to sustain crop growth, a poor structure, and a low water retention rate. Numerous elements, including drainage, depth, and profile development, affect the formation of the BRIS soil.